STUDIES IN CYPERACEAE. XIV. ENDOMORPHIC EVIDENCES FOR PLACING CYPERUS HYALINUS UNDER THE NEW SUBGENUS QUEENSLANDIELLA - E. GOVINDARAJALU (REINWARDTIA, 1975)
Detailed morphological and anatomical investigations of Cyperus hyalinus Vahl were undertaken and based on the data accumulated Queenslandiella Domin was accorded a new status as Cyperus L. subgen. Queenslandiella (Domin) Govindarajalu on a par with subgen. Cyperus, Mariscus, Kyllinga and Pycreus of the genus Cyperus.